HUBUNGAN DUKUNGAN EMOSIONAL DAN DUKUNGAN SOSIAL DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Dwi Fitriyanti; Novy Hari Yono; Rya Setyorini (NHM PRESS, 2022)
Hypertension is one of the degenerative disease, generally blood presure increases slowly with age, the prosess of controlling blood pressure cannot be separated from the role of the family, support from the closest is needed to help overcome hypertension. The aim of the study was to determine the relationship between emotional support and social support with blood pressure in hypertension patients. The research method uses a quantitative research design with a cross sectional approach. The population is the number of visits by hypertension patients. Total population 68 patients. The sampling technique used was purposive sampling, with a total of 61 samples. Collecting data using a questionnaire then the data that has been collected is prosesse using computer assistance using the spearmen test. The result of the study where emotional support with blood pressure obtained p-value = 0,004 and social support with blood pressure obtained p-value = 0,001. Conclusion there is a relationship between emotional support an social support with blood pressure in hypertension patients.